Pengaruh Beban Kerja dan Stress Kerja terhadap Kinerja Staf Pengajar Politeknik Negeri Pontianak - Evi Sofiana; Tri Wahyuarini; Syarifah Noviena (Politeknik Negeri Bengkalis, 2020)
Pontianak State Polytechnic (Polnep) is one of the higher vocational Institution in West Kalimantan. One of Polnep’s objective is to carry out various fields of vocational education in order to generate quality alumni. Achieving this objective requires hardwork and lecturer play a significant role. Since they play a significant role, the lecturer’s perfomance should be taken care of. There are 241 lecturer dan 140 of them have additional work in other unit besides teaching. Based on early observation, They are called Lecturer with additional work, which means they have to spare their time in campus not only for teaching buat also doing some additional work, so sometimes they tend to leave class. Based on early observation, they do the replacement class, late in submitted exam paper dan students grades. They also tend to give more assignment to students. This research purpose is to examine empirically the effect of Polnep lecturer’s workload to performance, and the effect of work stress to performance and the effect of workload to work stress. The research method is survey by using questionnaire as data collecting method. Samples were choosen with non probability sampling method, specifically purposive sampling. Based on first hypothesis testing, there is no proof about the effect of Polnep lecturer’s workload to performance which marked by sig. value 0.740. The same result happen to second hypothesis testing, there is no proof about the effect of Polnep lecturer’s work stress to performance which marked by sig. value 0.179. The third hypothesis testing proves the effect of workload to work stress. This resultmarked by sig. value of 0.000.